Studies of Alcohol-Amine Complexation by Dielectric Measurements - Pande, Rekha; Kalamse, G.M. (Asian Journal of Chemistry, 2016)
Using Surber’s technique of measuring reflection coefficient from the air-dielectric boundary of the liquid, the dielectric constant (e'), dielectric loss (e") of trigol, ethylene diamine, and their binary mixtures for different mole fractions of ethylene diamine in the mixture have been measured at 9.84 GHz. Density, viscosity and square of refractive index of binary mixtures, including those of pure liquids are reported. The values of dielectric parameters (e', e") have been used to evaluate the molar polarization (p12) and the excess permittivities (De', De"). Excess square refractive index, viscosity and activation energy of viscous flow have also been estimated. These parameters have been used to explain the nature of complex formation. The computed values of excess parameters have been fitted to the Ridlich-Kister relation to estimate binary coefficient and standard deviation.